Предмет: Алгебра,
автор: anyutariabkowa
Упростите выражение
а(а+5б)-(а+б)(а-б)
3а(а-2)-(а-3)квадрате
Ответы
Автор ответа:
0
a(a +5b) -(a +b)(a -b) =a² +5ab -(a² -b²) =a² +5ab -a² +b² =5ab +b²
3a(a -2) -(a -3)² =3a² -6a -(a² -6a +9) =3a² -6a -a² +6a -9 =2a² -9
3a(a -2) -(a -3)² =3a² -6a -(a² -6a +9) =3a² -6a -a² +6a -9 =2a² -9
Похожие вопросы
Предмет: Физика,
автор: maribachinska
Предмет: Алгебра,
автор: anabalanovskaa4
Предмет: Русский язык,
автор: ewdfrgtbny
Предмет: Математика,
автор: annailiadi128
Предмет: Геометрия,
автор: Аноним